In pursuit of the triple crown: mechanism-based pharmacodynamic modelling for the optimization of three-drug combinations against KPC-producing Klebsiella pneumoniae. (September 2020) - Onufrak, N.J.; Smith, N.M.; Satlin, M.J.; Bulitta, J.B.; Tan, X.; Holden, P.N.; Nation, R.L.; Li, J.; Forrest, A.; Tsuji, B.T.; Bulman, Z.P.
Abstract: Objectives: Optimal combination therapy for Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-Kp) is unknown. The present study sought to characterize the pharmacodynamics (PD) of polymyxin B (PMB), meropenem (MEM) and rifampin (RIF) alone and in combination using a hollow fibre infection model (HFIM) coupled with mechanism-based modelling (MBM). Methods: A 10-day HFIM was utilized to simulate human pharmacokinetics (PK) of various PMB, MEM and RIF dosing regimens against a clinical KPC-Kp isolate, with total and resistant subpopulations quantified to capture PD response. A MBM was developed to characterize bacterial subpopulations and synergy between agents. Simulations using the MBM and published population PK models were employed to forecast the bacterial time course and the extent of its variability in infected patients for three-drug regimens. Results: In the HFIM, a PMB single-dose ('burst') regimen of 5.53 mg/kg combined with MEM 8 g using a 3-hr prolonged infusion every 8 hr and RIF 600 mg every 24 hr resulted in bacterial counts below the quantitative limit within 24 hr and remained undetectable throughout the 10-day experiment. The final MBM consisted of two bacterial subpopulations of differing PMB and MEM joint susceptibility and the ability to form a non-replicating, tolerant subpopulation. Synergistic interactions between PMB, MEM and RIF were well quantified, with the MBM providing adequate capture of the observed data. Discussion: An in vitro – in silico approach answers questions related to PD optimization as well as overall feasibility of combination therapy against KPC-Kp, offering crucial insights in the absence of clinical trials.